the Capacity of the Local Government of Muna Regency in Addressing the Waste Management Issues in Raha City: KAPASITAS PEMERINTAH DAERAH KABUPATEN MUNA DALAM MENANGANI MASALAH SAMPAH DI KOTA RAHA - AMAS, MUHAMAD HAMASY RABWAL MAANI; Fauzan (LPPM STISIP IMAM BONJOL, 2025)
Waste management is a major challenge in urban environmental governance, including in Raha City, Muna Regency. This issue reflects the extent to which the local government is capable of providing effective, efficient, and sustainable public services. This study aims to analyze the capacity of the Muna Regency Government in managing waste in Raha City by examining institutional structure, human resources, infrastructure, funding, and community participation. The research employs a descriptive qualitative approach, utilizing data collection methods such as interviews, field observations, and document analysis. The results show that the local government's capacity still faces various obstacles, including a limited number of waste transport vehicles, insufficient budget allocation, and lack of coordination among related agencies. Furthermore, public awareness regarding waste sorting and proper disposal remains low. This study recommends strengthening institutional frameworks, enhancing the competence of government personnel, increasing waste management facilities, and encouraging active community involvement through educational and collaborative approaches. These findings are expected to provide input for local policy-making to improve sustainable urban environmental governance in Raha City.